(untitled) (Orfeu, 2017)
This work is a second reflection on the Inversional Projections Network, a concept presented previously in our article “Inversional Projections Network, Relationship between Tonnetze of Different Tricords” (ALBUQUERQUE, SALLES: 2017). We return here to our study of the scheme of harmonic organization developed to supply a model that could relate sets of different species and different cardinalities, a demand apparently not contemplated by traditional neo-Riemannian proposals. We built our system based on the concomitants between sets implicit in different Tonnetze, generated from inversions of all possibilities of tricords, revealing important symmetrical properties inherent to the chromatic universe in its full extension. We worked supported by the extensive discussion promoted by theorists dedicated to the development of specialized analytical tools for the study of the post- -tonal repertoire, focusing in particular on the consortium between parameters derived from musical set theory and neo-Riemannian theory.